WARRANT AND CONDITIONS FOR WARRANT IN ALVIN PLANTINGA’S PHILOSOPHY - MUSTAȚĂ, Gabriel (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Warrant and Conditions for Warrant in Alvin Plantinga’s Philosophy. Warrant is the central concept of Alvin Plantinga’s epistemology. As Plantinga suggests it, warrant is that quantity or quality which together with belief and truth constitutes knowledge. This paper intends to present broadly the concept of warrant and to analyze the conditions for warrant in order to see if the conditions proposed by Plantinga are necessary and sufficient for a belief to be considered knowledge.